Non-millennial teachers’ strategies in coping with the online teaching during the COVID-19 pandemic - Febry Khunto Sasongko; Diah Kristina; Abdul Asib (Universitas Syiah Kuala, 2022)
This article discusses the strategies used by five non-millennial teachers (aged 54-59 years old) of a junior high school in coping with the online teaching during the COVID-19 pandemic, in Ngawi, East Java, Indonesia. The teachers were interviewed, and the data were transcribed and analyzed by creating a data repository, expanding the codes, describing the coded data, and drawing conclusions. The results revealed that the teachers had several strategies used, which were to increase students’ interest in learning, provide students with knowledge and attention, create efficient learning resources, and use SIMPEL (Sistem Informasi Manajemen Pembelajaran or Learning Management Information System), which is specifically available only in Ngawi. SIMPEL was specially developed by the Ngawi district education office, to ensure that the learning processes in Ngawi Regency continue to run optimally during the COVID-19 outbreak. SIMPEL substituted the use of online YouTube videos and materials because the materials were already provided by the system, decreasing the need for the teachers to depend on other resources. Despite these teachers also using other online platforms, hence issues such as the slow internet connection, running out of quotas and blackouts, hindered their efforts to use these platforms at times. Hence, WAG was the most used media to conduct their online learning due to its simplicity and availability. These teachers continued to strive to learn digital technologies ever since they changed from their previous face-to-face teaching strategies.